The Economic Value of Personal Information and Policy Implication - Jiin Kim; Changi Nam; Seongcheol Kim (International Telecommunications Society (ITS), 2015)
Personal information is essential in an information-oriented society for societal development and as a valuable business resource. However, because of poor management and a lack of proper protection, leakage of personal information can take place over time, and the standard for compensation is not well established. In order to establish appropriate policies for its protection, we need to know the economic value of personal information. Using conjoint analysis, we analyze the potential value of personal information by calculating the marginal willingness to pay of Korean consumers for each attribute of personal information, which we estimate to be 7501.70 South Korean won (about 6.81 US dollars) per month. After indirectly estimating the economic value of personal information, we provide some political implications regarding the potential market size of any personal information protection service.
Keywords: 330; The value of personal information; Marginal willingness to pay; Conjoint analysis; Multinomial logit model